1991
DOI: 10.1038/jcbfm.1991.17
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Protein Kinase C-Dependent Smooth Muscle Contraction in the Pathogenesis of Chronic Cerebral Vasospasm

Abstract: Summary:In the present study, we investigate the pos sible role of protein kinase C (PKC)-dependent smooth muscle contraction in cerebral vasospasm following sub arachnoid hemorrhage (SAH), employing the beagle "two-hemorrhage" model. The occurrence of chronic va sospasm was angiographically confirmed on day 7 in the basilar artery, which was exposed via the transclival ap proach. The artery was superfused with aerated Krebs Henseleit solution containing various agents, and the sub sequent changes in the basil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…16 ET-1 induced a transient translocation of PKC activity from the cytosol to the membrane, and staurosporine reduced ET-1-induced contraction in bovine cerebral arteries. 17 The failure of calphostin C in reducing ET-1-induced contraction in this study is actually consistent with some previous reports that staurosporine and H-7 18 but not calphostin C 19 attenuated cerebral vasospasm in animal models. However, because of the discrepancy between the effects of staurosporine and calphostin C in this study, the role of PKC in ET-1-induced contraction in rabbit basilar artery remains unconfirmed and requires further investigation.…”
Section: Signal Transduction Pathways In Et-1-induced Contractionsupporting
confidence: 82%
“…16 ET-1 induced a transient translocation of PKC activity from the cytosol to the membrane, and staurosporine reduced ET-1-induced contraction in bovine cerebral arteries. 17 The failure of calphostin C in reducing ET-1-induced contraction in this study is actually consistent with some previous reports that staurosporine and H-7 18 but not calphostin C 19 attenuated cerebral vasospasm in animal models. However, because of the discrepancy between the effects of staurosporine and calphostin C in this study, the role of PKC in ET-1-induced contraction in rabbit basilar artery remains unconfirmed and requires further investigation.…”
Section: Signal Transduction Pathways In Et-1-induced Contractionsupporting
confidence: 82%
“…9,11 One of the hypotheses proposed for Ca 2ϩ sensitization in vascular smooth muscle involves PKC, a group of enzymes that are broadly engaged in vital cellular functions, including smooth muscle contraction. 12 The concept of a role for PKC in cerebral vasospasm is supported by the observations that phorbol esters, potent activators of PKC, induce angiographic vasospasm, 13 and that the PKC inhibitors improve the outcome in experimental models of vasospasm. 14 Whether PKC activation may initiate vasospasm is unclear, but an important step may be the phosphorylation of CPI-17 (PKC-potentiated phosphatase inhibitory protein of 17 kDa), an inhibitor protein involved in the regulation of MLCP.…”
mentioning
confidence: 75%
“…It was recently reported that TRPM4 is present in the pulmonary artery smooth muscle (50), consistent with the possibility that PKC-dependent activation of TRPM4 could contribute to HPV. A number of studies report that PKC inhibitors block or attenuate cerebral vaso-spasm in models of subarachnoid hemorrhage (30,31), suggesting that PKC activity has a prominent role in the development of this pathology (21). Our findings that PKC activates TRPM4 in cerebral artery vascular smooth muscle, which serves to depolarize these cells and induce vasoconstriction, are consistent with a potential role for the channel in PKCrelated vascular pathologies and suggest that TRPM4 might be a novel, putative pharmacological target for the treatment of such conditions.…”
Section: Discussionmentioning
confidence: 99%